IRONY AS A COMPLEX COGNITIVE MECHANISM - Djumaniyazov Doniyor Aleksandrovich (International Journal of Literature and Language Studies, 2026)
Irony is a complex pragmatic phenomenon that occupies a central place in human communication. This article examines the cognitive foundations of irony, the mental mechanisms involved in its comprehension — namely Theory of Mind, metarepresentation, and inferential reasoning — as well as its pragmatic and social functions. The study aims to analyse irony as a complex cognitive mechanism and to illuminate its role in human cognition on the basis of recent findings in cognitive linguistics, pragmatics, and neuroscience. The analysis draws on a theoretical-descriptive method and is supported by examples from Uzbek language data. The results demonstrate that comprehending irony requires higher-order cognitive capacities, and that this process varies according to cultural and contextual factors.